Injury and Illness Surveillance in Para-Cycling: A Single-Centre One-Season Prospective Longitudinal Study - Thomas Fallon; Paul Carragher; Neil Heron (Sports)
Introduction: Para-cycling is a competitive sport governed by the World Body for Cycling, Union Cycliste Internationale (UCI), encompassing various cycling disciplines tailored to athletes with physical or visual impairments. This study aimed to prospectively monitor the incidence of injury and illness in Para cyclists during the 2024 Paralympic season. Methods: This prospective, observational study included ten professional Para cyclists (five male, five female) with impairments ranging from spinal cord-related, neuromuscular, and musculoskeletal conditions to vision impairment. The definitions of an ‘athlete health problem’, ‘injury’, and ‘illnesses’ followed the Para sport translation of the IOC consensus. Injury and illness data were collected weekly using the Oslo Sports Trauma Research Centre Questionnaire on Health Problems V2 (OSTRC-H2), with the addition of subjective markers of well-being and training load, between February 2024 and October 2024. All medical contacts for any injury or illness were logged in line with consensus statement recommendations. Results: The OSTRC-H2 questionnaire had a response rate of 76.5% (±12.2%, range 55–88%) across the 35 weeks. Athletes reported 7.36 (95% CI: 5.41–9.46) health problems per 365 days, with a medical attention rate of 5.56 (95% CI: 3.91–7.36) per 365 days. The overall injury rate was 1.94 per 365 athlete days (95% CI: 1.23–2.93), with a higher incidence in males (2.44, 95% CI: 1.53–3.67) than in females (1.51, 95% CI: 0.68–2.95). Conversely, illness rates were higher in females (5.40, 95% CI: 3.00–8.11) than in males (1.80, 95% CI: 0.60–3.30), with an overall illness rate of 3.60 per 365 days (95% CI: 2.29–5.10). Conclusions: This is the first study to present prospective injury and illness epidemiology rates in Para cyclists in combination with subjective well-being markers. The findings underscore the importance and feasibility of longitudinal health monitoring in Para cyclists, ensuring that both physical and mental health concerns are systematically tracked and addressed. This enables a proactive, multidisciplinary support system to respond effectively to fluctuations in well-being, particularly during periods of injury or illness.